Phenological variation of leaf functional traits within species - Fajardo, Alex; Siefert, Andrew (Oecologia, 2016)
A basic assumption of the trait-based approach in plant ecology is that differences in functional trait values are greater between species than within species. We questioned this assumption by assessing (1) the relative extent of inter- and intraspecific leaf trait variation throughout a complete growing season (phenological variation) in a group of deciduous and evergreen woody species, and (2) whether species rankings based on leaf traits were maintained across the growing season. We analysed leaf mass per area (LMA) and leaf nutrient concentrations (C, N, P), including the C:N and N:P ratios. Intraspecific trait variation (ITV) due to phenology was significantly greater than interspecific variation for leaf N concentration on a mass basis (Nₘ; 68.90 %) and for the leaf C:N ratio (60.60 %), whereas interspecific variation was significantly higher than ITV for LMA (62.30 %) and for leaf C concentration on a mass (Cₘ) and area (Cₐ) basis (Cₘ 70.40 %; Cₐ 65.30 %). ITV was particularly low for LMA (<20 %). Species rankings were highly modified by phenology for a number of leaf traits (Pₘ, N:P ratio) but were relatively well conserved throughout the growing season for others (LMA, Nₘ). Patterns of ITV across the growing season differed significantly between deciduous and evergreen species for all traits except leaf P but did not vary between native and exotic species. Overall, our results show that intraspecific phenological variation in leaf traits may be similar to or greater than interspecific variation and that temporal patterns of ITV vary considerably among traits and species, especially for leaf nutrient concentrations, factors which can potentially affect quantitative interspecific relationships.